Trouble Shooting for Recalcitrant Bud Formation in Capsicum annuum var. Kulai - Mok, S.H.; Khalid, Norzulaani (Malaysian Society for Molecular Biology and Biotechnology, 2007)
hypocotyls and cotyledons of Capsicum annuum var Kulai from 8-14 days old seedlings were cultured on MS medium supplemented with various concentrations of BAP and IAA. Effect of explant types, developmental stages of seedling and duration of subculture in different media were studied. Young tissue from hypocotyls formed more buds than the older tissue. Hypocotyls showed better response than cotyledons. Subculture was carried out every two weeks to prevent browning of explants and promote adventitious bud formation and development. Optimal bud forming efficiency in hypocotyl explants was obtained when explants were cultured on MS media containing 3 mg/l BAP and 0.3 mg/l IAA for 2 weeks followed by subculture on medium supplemented with 2mg/l BAP and 0.15mg/l IAA. The percentage of bud formation was 75.48 Â± 4.71 .